Restraint stress induced anxiety and sleep in mice - Xu, Yong-Xia; Liu, Guo-Ying; Ji, Zhang-Zhang; Li, Yue-Yun; Wang, Yan-Li; Wu, Xue-Yan; Liu, Jun-Lin; Ma, Dan-Xia; Zhong, Ming-Kui; Gao, Chao-Bing; Xu, Qi (Frontiers in Psychiatry, 2023)
In humans and animals, exposure to changes in internal or external environments causes acute stress, which changes sleep and enhances neurochemical, neuroendocrine, and sympathetic activities. Repeated stress responses play an essential role in the pathogenesis of psychiatric diseases and sleep disorders. However, the underlying mechanism of sleep changes and anxiety disorders in response to acute stress is not well established. In the current study, the effects of restraint stress (RS) on anxiety and sleep–wake cycles in mice were investigated. We found that after RS, the mice showed anxiety-like behavior after RS manipulation and increased the amounts of both non-rapid eye movement (NREM) and rapid eye movement (REM) sleep in the dark period. The increase in sleep time was mainly due to the increased number of episodes of NREM and REM sleep during the dark period. In addition, the mice showed an elevation of the EEG power spectrum of both NREM and REM sleep 2 h after RS manipulation. There was a significant reduction in the EEG power spectrum of both NREM and REM sleep during the darkperiod in the RS condition. The expression of the c-Fos protein was significantly increased in the parabrachial nucleus, bed nucleus of the stria terminalis, central amygdala, and paraventricular hypothalamus by RS manipulation. Altogether, the findings from the present study indicated that neural circuits from the parabrachial nucleus might regulate anxiety and sleep responses to acute stress, and suggest a potential therapeutic target for RS induced anxiety and sleep alterations.